Natural and Social Science Learning Module Based on Augmented Reality Technology Containing Ecoliteracy in the Independent Curriculum in Elementary Schools - Narulita, Nidya; Yanita Sari, Yessy; Fatayan, Arum (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
The lack of contemporary technology-based teaching materials and also the integration of environmental literacy in IPAS subjects in elementary schools results in low learning outcomes of IPAS elementary school students and also low awareness of protecting the surrounding environment. This research aims to develop an Augmented Reality (AR) technology-based IPAS learning module with ecoliteracy content in order to support the implementation of the Merdeka Curriculum in elementary schools. This module is designed to improve students' understanding of complex scientific concepts and improve students' environmental literacy skills. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The developed module was tested by media experts and material experts. The results of the media expert test showed an average score of 3.63 from the display aspect and 3.73 from the usage aspect, which was included in the very good criteria. The material expert assessment gave a score of 3.49 from the content aspect and 3.53 from the learning aspect. In addition, the effectiveness of this module was tested using ecoliteracy questions. The results of gain testing showed a significant increase in students' ecoliteracy. Thus, the results of this study indicate that the IPAS learning module based on augmented reality technology with ecoliteracy content can improve the quality of interactive and contextual learning in elementary schools, in accordance with the principles of the Merdeka Curriculum. This module not only facilitates understanding of complex IPAS concepts through attractive visualizations but also fosters students' ecological literacy from an early age.